EXPERIMENTAL STUDY OF GRANULAR CONVECTION ON PSEUDO TWO-DIMENSION AND TWO-DIMENSION BRAZIL-NUT EFFECT - ANGGIT CAHYO WIBOWO (NIM : 90213008), HARI
Brazil-Nut Effect (BNE) experiment in pseudo two-dimension and two-dimension are conducted. In observing the BNE in pseudo two-dimension small spherical beads are used as bed particles, while small acrylic disks are used in the two-dimension. In both experiments the container box is made form acrylic. The first experiment shows that convection flow of the granular particles decreases with the increase of frequency in the range of 17-22 Hz at constant vibration voltage 10 V. It is also observed that intruder rise time Trise increases with the increase of frequency in the range of 13-18 Hz. This holds for vibration voltage 10, 11 and 12 V. The second experiment is conducted for frequency in the range of 13-17 Hz and normalized acceleration Γ: 2; 2,5; 3; 3,5; 4. Two different states are observed. In the former state Trise decreases with the increase of Γ, while in the later one it increases due to the existence of Leidenfrost effect.